Technical diversity in the work of scientific models Natural history museum as a model (Journal of the College of Basic Education, 2019)
The current research presents (Technical diversity in the art of scientific societies), the state of the art of societies in presenting diverse objects, subjects and environments from the field of knowledge and science in visual form, formative representation and visual presentation that invests and employs the technical diversity of materials and materials. Therefore, the researcher presented in the first chapter the problem of research and reaching the goal of research in the detection of technical diversity in the art of scientific societies, Chapter two, the researcher divided the chapter into two sections: the first topic: the art of the communities characteristics and characteristics. The second topic: diversity of use in the art of societies, The researcher follows the forms and characteristics of the art of societies and diverse uses in the fields of knowledge and science and investment of the diversity of materials and raw materials in the construction of the external appearance, In the third chapter, the researcher presented an applied sample of the marsh environment, showing its biological diversity, and the environment of the water caves. The researcher used materials such as wood, cork and wire, and showed the aquatic environment of the rivers and oceans to provide an environment that surrounds the Silencath fish, which are extinct fish. They are from the reservoirs of the Natural History Museum, Baghdad, As for the fourth chapter, the researcher reached conclusions, including that the art of societies provide a concept that is difficult to comprehend in the society or student of art or medicine or the rights of knowledge of its diversity, And highlights the technical diversity in the art of communities, especially in the museums of natural history and the arrangement of objects, birds and animals in an environment contribute to the aesthetic organization of the imagination of the recipient, The technical diversity in the art of societies provides an optical system that addresses the eye and the mind as a cultural field that interacts with its neighbors of science and knowledge fields. The researcher then presented recommendations and suggestions.